2018
DOI: 10.3390/ijerph15020199
|View full text |Cite
|
Sign up to set email alerts
|

Undertaking a Collaborative Rapid Realist Review to Investigate What Works in the Successful Implementation of a Frail Older Person’s Pathway

Abstract: We addressed the research question “what factors enable the successful development and implementation of a frail older person’s pathway within the acute setting”. A rapid realist review (RRR) was conducted by adopting the RAMESES standards. We began with a sample of 232 articles via database searches supplemented with 94 additional records including inputs from a twitter chat and a hospital site visit. Our final sample consisted of 18 documents. Following review and consensus by an expert panel we identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
(96 reference statements)
1
24
0
Order By: Relevance
“…[54] Future research should also focus on contextual factors supporting frailty interventions, such as health resources provisioning, [55] linkages between acute and long-term care services, [56] configuration of care packages, [57] and public and patient involvement in co-designing interventions. [58] There is also some incompatibility between frailty measures themselves, necessitating caution in comparing outcomes.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…[54] Future research should also focus on contextual factors supporting frailty interventions, such as health resources provisioning, [55] linkages between acute and long-term care services, [56] configuration of care packages, [57] and public and patient involvement in co-designing interventions. [58] There is also some incompatibility between frailty measures themselves, necessitating caution in comparing outcomes.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…When a person registers to a Twitter account other users can follow them and see their tweets. Previous work has found that analysis of the content on social media has become a valuable source of information for health researchers [25][26][27] The information provides researchers with publicly available data that would not be accessible using more traditional methods for data collection [28]. Previous work has highlighted that peer interaction on social networks such as Twitter can contribute to policy development in health and social care [28,29].…”
Section: Breadthmentioning
confidence: 99%
“…Our focus within the ‘Systematic Approach to improving care for Frail older patients’ (SAFE) study was to co-design quality improvement initiatives within an integrated care pathway for frail older people in an acute setting [2]. As part of the SAFE study we undertook a review of the literature to capture what works in the successful implementation of a frail older person’s pathway [14]. A significant finding in the review was the absence of methodological studies which include patients and public groups in the co-design of frailty interventions and in the identification of priority areas for improvement initiatives.…”
Section: Introductionmentioning
confidence: 99%